A supramolecular assembly of metal-free organic dye with zinc porphyrin chromophore for dye-sensitized solar cells. Issue 43 (25th October 2017) - Jia, Hai-Lang; Huang, Mao-Zhan; Peng, Zhi-Jie; Wang, Dong-Ming; Zhang, Guo-Hua; Guan, Ming-Yun
Abstract : The supramolecular system has superior performance in improving spectral response and reducing charge recombination, which could be a promising and convenient method to improve the performance of DSSCs. Abstract : Two porphyrin chromophores, P1 and P2, were prepared and used as antenna units to coordinate with a metal-free organic dye, JH1, containing pyridine groups. This supramolecular self-assembly strategy can not only effectively improve the light-harvesting ability of the devices but also effectively reduces electron recombination by preventing I3 − of the electrolyte from penetrating into the TiO2 surface. The DSSC based on JH1 showed a PCE of 2.46%, with a V oc of 615 mV, J sc of 6.54 mA cm −2, and FF of 61.18%. After supramolecular self-assembly, the J sc and V oc of the device were greatly improved. Specifically for the device based on JH1 + P2, the PCE reached 4.39%, which is about 78% greater than the PCE of the device based on JH1; this is mainly due to the J sc increase of 2.85 mA cm −2 and the V oc increase of 93 mV. Compared to co-sensitization, supramolecular self-assembly does not require tedious optimization steps; thus, this may be a promising and convenient way to improve the overall performance of DSSCs.